Regulatory T cells in the peripheral blood of women with gestational diabetes: a systematic review and meta-analysis - Arain, Hania; Patel, Tina; Mureanu, Nicoleta; Efthymiou, Athina; Lombardi, Giovanna; Tree, Timothy; Nicolaides, Kypros H.; Shangaris, Panicos (Frontiers in Immunology, 2023)
Background: Gestational diabetes (GDM) affects approximately 14% of pregnancies globally and is associated with short-and long-term complications for both mother and child. In addition, GDM has been linked to chronic low-grade inflammation with recent research indicating a potential immune dysregulation in the pathophysiology, and a disparity in regulatory T-cells.Objective: This systematic review and meta-analysis aimed to determine whether there is an association between GDM and the level of Tregs in the peripheral blood.Methods: Literature searches were conducted in PubMed, Embase and Ovid between the 7 th and 14 th February 2022. Inclusion criteria were any original studies published in the English Language, measuring differentiated Tregs in women with GDM, compared to glucose-tolerant pregnant women. Meta-analysis was performed between comparable Treg markers. Statistical tests were used to quantify heterogeneity: Tau 2 , X 2 and I 2 . Study quality was assessed using a modified version of the Newcastle-Ottawa scale.The search yielded 223 results: eight studies were included in the review and seven in the Meta-analysis (GDM = 228, Control = 286). Analysis of Tregs across all trimesters showed significantly lower Treg numbers in women with GDM (SMD, -0.76; 95% CI, -1.37, -0.15; I 2 = 90%). This was reflected in analysis by specific Treg markers (SMD -0.55; 95% CI, -1.04, -0.07; I 2 = 83%; third-trimester, five studies). Non-significant differences were found within subgroups (differentiated by CD4+FoxP3+, CD4+CD127-and CD4+CD127-FoxP3) of both analyses.GDM is associated with lower Treg numbers in the peripheral maternal blood. In early pregnancy, there is clinical potential to use Treg levels as a predictive tool for subsequent development of GDM. There is also a potential therapeutic intervention to prevent the development of GDM by increasing Treg populations. However, the precise mechanism by which Tregs mediate GDM remains unclear.